Implementasi Model Pemberdayaan Perempuan Berbasis Pengembangan Industri Rumah Tangga Spesifik Lokal Di Kabupaten Karangasem, Provinsi Bali - Ni Wayan Sri Astiti; Dwi Putra Darmawan; I Dewa Gede Raka Sarjana (Universitas Udayana, 2017)
Abstract Implementation of the Women Empowerment Model Based on Develompment of Household Industrial Specific Local in Karangasem Regency, Bali Province Empowerment model obtained by Analytic Network Process (ANP) proposed a top priority industrial development strategy of household handicraft is through strengthening human resource competencies. Based on these results, the objectives of the activities are (1) to develop business institutions elected, namely the Joint Business Group (the Kube) in the handicraft industry of coconut shell, (2) increase the capabilities of businesses in terms of production management and marketing, (3) strengthen the institutional in order to the business groups able to utilize the facilities and production technology, as well as improving product marketing functions, and (4) develop a system of household handicraft industry in an integrated manner, supported by marketing management information system based on the web. The research location is the Kube named